Morphological characterization of the renal vein in pigs (Sus domesticus). Differential analysis with the human renal veins (2017)
Despite its importance as an experimental model, information about the morphology of the renal vein (RV) is scarce and limited to qualitative descriptions. The objective of this investigation was to determine the morphological characteristics of the RV and its tributaries in pigs (Sus domesticus). We studied 93 pairs of kidneys of pigs destined to slaughter. This descriptive study evaluated the RV and its tributaries, which were perfused with polyester resin (85% Palatal and 15% styrene). Subsequently for full corrosion pieces were subjected to infusion of KOH (potassium hydroxide) for 10 days. The RV and their tributaries were assessed for shape, trajectory and morphometry. The level of significance was set at p < 0.05. A single RV was found in 93% of the specimens. The caliber of the RV was 12.8±3.05 mm. It was significantly higher on the left side (p = 0.043). Length was 26.54±12.81 mm for the right RV and 37.64±13.62 mm for the left RV. The position of the RV in relation with the renal artery was cranial-ventral in 46.2% of the specimens, whereas its origin was hilar in 61.9% of the cases. The emergence of the RV from two tributary veins (pattern Ia) was the most common (76.9%). The morphological characteristics of the VR observed in this study are similar to those reported in humans, so the usefulness of this animal model in procedural applications and hemodynamics is evident.